Problematika dan Perkembangan Pasar Modal Syariah di Indonesia - Hendra, Wiwi Widia Argita (Islamic Economics and Business Review, 2024)
Abstract In Indonesia, the sharia capital market has experienced rapid growth in line with increasing demand for sharia investment instruments. However, with the development of the Islamic capital market, various problems and challenges have emerged that need to be overcome. This study discusses the problems and development of the Islamic capital market in Indonesia with a focus on development efforts, regulatory changes and the challenges faced. The central problem is the lack of supportive regulations, thus hindering wider investment in the sharia capital market and also the lack of public literacy or knowledge of the sharia capital market is also an obstacle to the development of the sharia capital market in Indonesia. The aim of this research is to achieve an in-depth understanding of the problems and development of the Islamic capital market towards an efficient capital market. Research results The development of the sharia capital market can be seen from the development of instruments including sharia shares, sharia bonds and sharia mutual funds. This third instrument also continues to increase, although conventional remains superior, but does not reduce the performance of the sharia capital market and the interest of investors who choose sharia capital market instruments. Keyword: Problems, Sharia Capital Market, Development Abstrak Di Indonesia, pasar modal syariah telah mengalami pertumbuhan pesat seiring dengan meningkatnya permintaan terhadap instrumen investasi syariah. Namun dengan berkembangnya pasar modal syariah, muncul berbagai permasalahan dan tantangan yang perlu diatasi. Kajian ini membahas permasalahan dan perkembangan pasar modal syariah di Indonesia dengan fokus pada upaya pengembangan, perubahan peraturan dan tantangan yang dihadapi. permasalahan sentralnya adalah kurangnya regulasi yang mendukung, sehingga menghambat investasi yang lebih luas di pasar modal syariah dan juga kurangnya literasi atau pengetahuan masyarakat terhadap pasar modal syariah juga menjadi kendala terhadap perkembangan pasar modal syariah di indonesia. Tujuan penelitian ini adalah untuk mencapai pemahaman yang mendalam tentang problematika dan perkembangan pasar modal syariah menuju pasar modal yang efisien. Hasil penelitian Perkembangan pasar modal syariah dapat dilihat dari perkembangan instrumennya diantaranya saham syariah, obligasi syariah dan reksadana syariah. Ketiga instrumen ini juga terus mengalami peningkatan meskipun tetap saja konvensional lebih unggul tetapi tidak mengurangi kinerja pasar modal syariah dan minat para investor yang memilih instrumen pasar modal syariah. Kata kunci : Problematika, Pasar Modal Syariah, Perkembangan